Uganda's new Governor, Sir Frederick Crawford,K.C.M.G, O.B.E,shaking hands with Mr.C.H.Bird, Minister of commerce and works.To the right of Mr.Bird are C.H. Haetwell,Chief Secretary and Mr.R.L.E Dreshfield ,Att orney Generel.Also in the picture are Mr.A.K Kironde ,Asst.Minister of Social Services , and Mrs.Kironde.Sir Frederick arrived at Entebbe Airp ort on February 26t and was later sworn in as Governor and Commander in chief of the protectorate.
Shelf no.
Uganda's new Governor, Sir Frederick Crawford,K.C.M.G, O.B.E,shaking hands with Mr.C.H.Bird, Minister of commerce and works.To the right of Mr.Bird are C.H. Haetwell,Chief Secretary and Mr.R.L.E Dreshfield ,Att orney Generel.Also in the picture are Mr.A.K Kironde ,Asst.Minister of Social Services , and Mrs.Kironde.Sir Frederick arrived at Entebbe Airp ort on February 26t and was later sworn in as Governor and Commander in chief of the protectorate.
AR/MAK PHOTOS/28/67
English
Keywords: Photos of Uganda